2019
DOI: 10.1111/jfbc.13023
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of CaMKKβ‐mediated AMPK activation on the glycolysis and the quality of different altitude postmortem bovineslongissimusmuscle

Abstract: This study investigated the activity of adenosine monophosphate‐activated protein kinase (AMPK), glycolysis, and meat quality index in three altitude bovines during postmortem aging process. Local cattle (altitude:1,500 m), Gannan yak (3,000 m), and Yushu yak (4,500 m) postmortem Longissimus Dorsi (LD) muscle were used. Results indicated that CaCl2 significantly increased the AMPK activity by increasing the calcium‐regulated protein kinase kinase (CaMKKβ) activity. Besides, AMPK activation enhanced the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 51 publications
4
14
0
Order By: Relevance
“…3 , it can be demonstrated that ROS is essential for the accumulation of HIF-1α, which further regulates the activation of key glycolytic enzymes (HK and PFK) to enhance glycolytic potential early postmortem. Our results are partly consistent with those of Gao et al (2019) , who indicated that the greater glycolytic enzyme activity and glycolysis rate of yak meat within 24 h postmortem are attributed to its higher expression level of HIF-1α.
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…3 , it can be demonstrated that ROS is essential for the accumulation of HIF-1α, which further regulates the activation of key glycolytic enzymes (HK and PFK) to enhance glycolytic potential early postmortem. Our results are partly consistent with those of Gao et al (2019) , who indicated that the greater glycolytic enzyme activity and glycolysis rate of yak meat within 24 h postmortem are attributed to its higher expression level of HIF-1α.
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…These results not only showed that YC‐1 could inhibit the decrease in pH but also indicated that HIF‐1α was related to the decrease in pH during postmortem aging. The observations were consistent with those of Gao et al (2019) who pointed out that the pH value was inversely proportional to the altitude where the yaks grow and that it reached its lowest value at 72 hr. HIF‐1α guides the glycolysis pathway by promoting the expression of glucose transporters and glycolytic enzymes and by decreasing the pH value (Gordan et al, 2007), with the mitochondria also increasing the rate of pH and ATP decline (Hudson et al, 2012).…”
Section: Resultssupporting
confidence: 92%
“…These results were consistent with those reported by Soñanez-Organis et al (2012), where the silencing of HIF-1α inhibited the increase of LDH activity produced by a cell under hypoxic conditions. In addition, Gao et al (2019) found that LDH and HK activities not only showed an upward trend prior to a downward one as the postmortem period of yak muscles increased but also that the activities were highest in high-altitude yaks. Shen et al (2014) also observed that high levels of mRNA for genes related to HK contributed to high glycogen content, glycolytic rate, and glycolytic potential (GP) in "fast-glycolytic-type" muscles.…”
Section: Effects Of Hif-1α Upregulation On Glut-1 and Glycolytic Enzymementioning
confidence: 94%
See 2 more Smart Citations